The causal nexus between international tourism and economic growth - Putu Mahardika Adi Saputra, Ni Luh Putu Muliadini, (Opción, 2019)
This study aims to determine whether there is a causality relationship between international tourism and economic growth in Bali Island via Granger and Toda-Yamamoto methods as the technique for testing the causality. The findings of the study confirm that there is significant evidence of three hypotheses related to the causal nexus between international tourism and economic growth in Bali. In conclusion, If the government of Bali wants to use the potential of international tourism as the main driver of its economic growth, then the Singapore market is a market that deserves to be given priority over other markets.